Hardly traceable pitfalls in medical review articles - Olaf R. van Loon; A.J. (Tom) (Elsevier, 2022)
The main purpose of review articles is to increase insight into the best possible practice for increasing the health condition of future subjects. This requires the collection of as many relevant data as possible from earlier case studies, but such data should be mutually independent. If the data from the reviewed single- or multi-case studies are not entirely mutually independent, the conclusions of the review study may easily - though not necessarily - become biased. This is shown on the basis of a 2020 systematic review about the effects of deep dry needling on spasticity and related physical disabilities. We analyzed this study by checking undisclosed possible overlaps regarding the subjects dealt with in the various case studies that were reviewed. This analysis raised also some questions about the accuracy of the number of subjects that had been treated, which is an aspects of which errors can commonly not be disclosed by the readers. The objective of our Letter is to show that insufficient attention by authors, editor and reviewers for an unambiguous presentation of the data regarding the subjects dealt with can make it impossible for readers to draw correct conclusions regarding the optimization of possible treatments.